2022
DOI: 10.7717/peerj.13615
|View full text |Cite
|
Sign up to set email alerts
|

PPBP gene as a biomarker for coronary heart disease risk in postmenopausal Thai women

Abstract: Background Estrogen is an important ovarian hormone with anti-atherogenic and cardioprotective effects. Postmenopausal women have lower estrogen levels, associated with significantly higher risks of coronary heart disease (CHD) and CHD-related death. Effective biomarkers for the diagnosis, prediction, and treatment of CHD are needed to address this problem and thus reduce the mortality due to CHD in postmenopausal women. We recently reported that the PPBP and DEFA1/DEFA3 genes may be feasible synergistic bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The results showed that both the mRNA and protein of PPBP were significantly higher in inflammatory gingival tissues in comparison to healthy controls. High expression of PPBP was found in the plasma or serum of various inflammatory, allergy, and cardiovascular disorders, 15 , 16 , 17 , 19 which raises the possibility that PPBP contributes to the host immune response. However, the relationship between PPBP and periodontitis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that both the mRNA and protein of PPBP were significantly higher in inflammatory gingival tissues in comparison to healthy controls. High expression of PPBP was found in the plasma or serum of various inflammatory, allergy, and cardiovascular disorders, 15 , 16 , 17 , 19 which raises the possibility that PPBP contributes to the host immune response. However, the relationship between PPBP and periodontitis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that PPBP is specifically elevated in the serum of Porphyromonas gingivalis -infected mice compared with sham-infected mice. 25 PPBP has been found in the plasma of people with diabetes mellitus, 15 coronary artery disease, 19 and the serum of people with rheumatoid arthriti. 17 It is believed to be a possible biomarker for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that altered expression of DDX58 [413], STAT1 [414], TLR4 [415], CYP2D6 [416], JAK2 [417], TLR2 [418], DUSP6 [419], HDAC9 [420], LATS2 [421], CA2 [150], HIPK3 [422], CCR2 [423], GAB1 [120], UFL1 [424], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [425], PRKAR1A [265], SIRT1 [426], FGL2 [427], TET2 [428], ASCC2 [429], BIN1 [430], HSPB1 [431], IGFBP4 [432], TRPM4 [433] and LGALS3 [434] might be associated with the progression of heart failure. STAT1 [435], TLR4 [436], ABCA1 [437], PTGS2 [68], CYP2D6 [438], CR1 [439], PDK4 [440], RNF213 [441], ZDHHC17 [70], TLR8 [442], PDGFC (platelet derived growth factor C) [443], TLR2 [444], CYP1B1 [445], HDAC9 [446], IL1RN [447], GCH1 [448], EGR1 [449], ZEB2 [450], PLA2G7 [451], CCR2 [452], GCLC (glutamate-cysteine ligase catalytic subunit) [258], VEGFA (vascular endothelial growth factor A) [453], CD46 [454], NFKBIZ (NFKB inhibitor zeta) [455], LDLR (low density lipoprotein receptor) [456], TLR6 [457], SIRT1 [458], NOD2 [459], FGL2 [460], IDH1 [461], TET2 [462], PFKFB2 [463], KDM6A [464], IKZF2 [465], ZNF606 [466], PF4 [467], CCR7 [468], RUNX3 [469], TCF7 [470], PPBP (pro-platelet basic protein) [471], IGFBP4 [280], HSPG2 [472] and LGALS3 [236] expression might be regarded as an indicator of susceptibility to CAD. STAT1 [473], TLR4 [367], JAK2 [474], PDGFC (platelet derived growth factor C) […”
Section: Discussionmentioning
confidence: 99%
“…CCC analysis further indicated the presence of a representative CXCL signaling pathway (i.e., the L–R pair of PPBP and CXCR2) in the C4_DEFA1/1B/3 population. The PPBP ligand, one of the signatures of the C4_DEFA1/1B/3 subtype in this study, is involved in various conditions; PPBP was detected in activated platelets that are involved in chronic inflammation during the development of atherogenesis and coronary heart disease (CHD), and thus could be used as a biomarker for CHD risk in postmenopausal Thai women [51]. Combined with PADI4 expression, PPBP expression may be considered a non-invasive multi-marker approach offering diagnostic and clinical value in patients with suspected lung cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…The PPBP ligand, one of the signatures of the C4_DEFA1/1B/3 subtype in this study, is involved in various conditions; PPBP was detected in activated platelets that are involved in chronic inflammation during the development of atherogenesis and coronary heart disease (CHD), and thus could be used as a biomarker for CHD risk in postmenopausal Thai women [51]. Combined with PADI4 expression, PPBP expression may be considered a non-invasive multi-marker approach offering diagnostic and clinical value in patients with suspected lung cancer [51]. Another study demonstrated that PPBP is a major repressive target of glucocorticoids that promote gluconeogenesis [52,53].…”
Section: Discussionmentioning
confidence: 99%